Uitbranding by die predikant: ’n Sistemiese perspektief - Muller, J. C. (Verbum et ecclesia, 1992)
Burnout amongst ministers of religion: A systemic perspective In contrast to fatigue or stress, burnout is a syndrome which is the result of a long process of imbalance between pressure and resources. The author argues that there are no simple solutions in crash courses or seminars on stress. The phenomenon of burnout can only be explained and resolved through a systems perspective. The pastor participates in two basic systems: the work and love system. When he experiences conflict between these two, it could easily lead to burnout. Except for resolving the problems within the systems, the ideal is for the pastor to participate in a third system, a system that functions as a peer group.